Multipurpose Training Tool Development Branch of Artistic Gymnastics (Medico Legal Update, 2021)
The majority of sports organizations including gymnastics in Central Java Province still use school arenaswhich are quite small and not representative according to the rules of the Federation Internationale deGymnastics (FIG). Meanwhile, athletes must train without the hindrance of external factors such as ourfacilities. Purpose of Study: To provide a solution that can be applied to a limited school area by conductingfield analysis and designing a suitable model, especially for uneven rods in gymnastics. The material inthis study is the school arena, the uneven bars. Observation and measurement are used to collect data,then analyze it using Computer Aided Design software. The data are presented as descriptive quantitative.Result: To facilitate uneven trunks it can be constructed using either a log or glass fiber with adjustable posts(lower: 1.61-1.70 meters; upper: 2.41-2.50 meters), and with grip properties such as tension: 13.64 Newton,displacement: 1.17 mm, strain: 4.428 m/m. Conclusion: The modified unmodified bar has been designed tooptimize training sessions in a limited school area.